Retinopathy in Preterm Low Birth Weight Babies and Special Management by Oxygen and Blood Transfusion (IAHS Medical Journal, 2026)
Background: More Occurrence of retinopathy of prematurity in preterm low birth weight babies exposed to different risk factors in Ad-din NICU is reported. The aim was to assess the Proportion of ROP development in different risk factor exposed group in a large cohort of very preterm infants who were assisted in Ad-din NICU. Aim of this study is to identify the most common risk factor and the severity of Retinopathy of Prematturity (RoP).Materials and methods: This prospective study was carried out at the level-3 NICU of Ad-din Medical College Hospital Dhaka. 53 preterm low birth weight baby who are